Sustainable management of olive rainfed orchards by the introduction of leguminous cover crops - Correia, Carlos M. (2013)
The olive sector has a crucial economic, social, cultural and ecological relevance in the Mediterranean region, where tillage and herbicides application are still generalized practices. However, these practices oppose the recommendations of UE Common Agricultural Policy and thus, management methods that decrease requirement for agricultural chemicals are needed to reduce adverse environmental impacts. Moreover, they can play an important role in atmospheric C01 emission and fixation. We propose green manure legumes to reduce erosion, soil compaction and nih·ate pollution, to improve biodiversity, soil carbon sink and fertility, to save fossil fuels and to increase yield and the safety and nutritional value of food products. The 3-yearfield study carried out in Northeast Portugal revealed that self-reseeding annual legumes is a promising strategy since increase the summer soil water content, the vegetative growth and the physiological tree pe1jormance, that was reflected in a 38% higher cumulative yield then tillage techniques.